A Study of the Introduction to Ibn Qutaybah al-Dinwari's Book of Knowledges (d. 276 AH/889 CE) - Hameedi Khudhair Jumaa (Zanco Journal of Human Sciences, 2025)
This study aims to highlight the quantitative or graphical analytical method in scientific research (Text analysis) and its application to historical texts. This is to understand the psychological or ideological motivations behind the written text, or to determine the motivation for authorship. By selecting a specific text and counting the number of words it contains, then identifying the ten most frequently occurring words in the text, and creating a percentage for each of the top ten words divided by the total number of words in the text, the role of the study becomes apparent. The study then provides an interpretation and reason for the frequent repetition of a particular word over others, and reveals the author's most important messages. The study was conducted on the introduction to Ibn Qutaybah al-Dinwari's Book of Knowledge (D. 276 AH/ 889 CE), as he was a renowned author who wrote on various sciences and played an active role in enriching intellectual currents in Islamic history, having lived and died in the third century AH. The study, conducted on the introduction to this famous literary work, highlighted the arrangement of knowledge according to the book's author. According to the statistics, issues of genealogy, kings, knowledge, and then science were his primary concerns or his understanding of the needs of scholars and society at that time.